Household wealth in the euro area: the importance of intergenerational transfers, homeownership and house price dynamics - Thomas Y. Mathä; Alessandro Porpiglia; Michael Ziegelmeyer (European Central Bank (ECB), 2014)
Results from the Eurosystem Household Finance and Consumption Survey reveal substantial variation in household net wealth across euro area countries that await explanation. This paper focuses on three main factors for the wealth accumulation process, i) homeownership, ii) housing value appreciation and iii) intergenerational transfers. We show that these three factors, in addition to the common household and demographic factors, are relevant for the net wealth accumulation process in all euro area countries, and moreover that, using various decomposition techniques, differences therein, in particular in homeownership rates and house price dynamics, are important for explaining wealth differences across euro area countries.
Keywords: D31; E21; O52; C42; 330; euro area; homeownership; household wealth; inheritance; property prices